Gerromorpha y Nepomorpha (Insecta: Heteroptera) del Parque Provincial Salto Encantado del Valle del Cuñá Pirú, Provincia de Misiones, Argentina (Lundiana: International Journal of Biodiversity, 2009)
A preliminary list of the species of semiaquatic and aquatic Heteroptera occurring in the Parque Provincial Salto Encantado del Valle del Cuñá Pirú is presented. Thirty species included in 13 genera and five families of Gerromorpha and 26 species belonging to 15 genera and six families of Nepomorpha were recorded; only 16 species had been previously cited from the park. Ten species and one genus are reported from Argentina for the first time: Microvelia argentata Nieser & Alkins-Koo, Microvelia braziliensis McKinstry, Microvelia limaiana Drake, Rhagovelia janeira Drake, Rhagovelia lucida Gould, Rhagovelia paulana Drake (Veliidae), the genus Cylindrostethus, with C. palmaris Drake & Harris (Gerridae), Curicta carinata Kuitert (Nepidae), Neotrephes lanemeloi Nieser & Chen, and Neotrephes usingeri China (Helotrephidae). Twenty-four species (18 of Gerromorpha and six of Nepomorpha) and five genera (Hebrus, Paravelia, Platyvelia, Cylindrostethus and Curicta) are reported from Misiones Province for the first time. The most diverse families included Veliidae (16 species), Gerridae (9), Naucoridae (7), Notonectidae (6) and Corixidae (5). The diversity of species inhabiting in the Parque Provincial Salto Encantado del Valle del Cuñá Pirú accounts for 83% of Gerromorpha and 39% of Nepomorpha recorded from the Misiones Province. These results emphasize the value of this protected area for the conservation of biodiversity of semiaquatic and aquatic Heteroptera occurring in the province.